Introduction of discrete phase model (DPM) in fluid flow: A review - Zahari N.M.; Zawawi M.H.; Sidek L.M.; Mohamad D.; Itam Z.; Ramli M.Z.; Syamsir A.; Abas A.; Rashid M. (American Institute of Physics Inc., 2023)
Involvement of important engineering applications in the interaction of free-moving objects with dispersed multi-phase flows are numerous in recent years. However, due to the challenge and complexity, few studies have been reported and modeling approaches remain very limited. This paper reviews the use of discrete particle models (DPMs) for the study of the fluid flow phenomena and elaborates several different types of multiple phases. The efficiency of particle retention and computational time were considered in determining the most appropriate multiphase model. Therefore, the dynamic modeling of multi-scale systems requires a method to solve the problem of structural fluid interaction (FSI) in the particle fluid flow. 2018 Author(s).